Blue planet law : the ecology of our economic and technological world - Garcia, Maria da Glória; Cortês, António (Sustainable development goals series,, 2023)
Blue Planet Law is the global and future-oriented environmental law that is necessary to face the global environmental crisis in the Anthropocene, assuming especially the link between climate action (SDG 13) and ocean sustainability (SDG 14). This open access book focuses on means of overcoming global environmental problems such as climate change, ocean degradation and biodiversity loss and the consequent risks for human life, health, food and wellbeing. It explores how environmental law, at the international, European and national levels, might set economic and technological development on a more sustainable path. Law must engage in dialogue with other areas such as philosophy, economics, ecology, and biology. This book highlights protection of the climate and the oceans and sustainable use of natural resources, through new policies, economies and technologies, including biotechnology, with a view to the preservation of life, health, food and a healthy environment for the present and future generations. The book may be seen as a contribution to the UN Sustainable Development Goals 13 and 14 and a tribute to the Declaration of the United Nations Conference on the Human Environment, also known as the Stockholm Conference (1972), on its 50th Anniversary.